Kepemimpinan Kepala Sekolah Dalam Emenrapkan Budaya Sekolah Terhadap Karakter Siswa - Lismanita Lismanita (Jurnal Administrasi Pendidikan dan Konseling Pendidikan, 2020)
This study discusses the principal's style leadership in relation to schools with their students'. This research to focused on the application of school culture and thought to students' characters through the leadership of the principal. This study discusses the principal in relation to schools and discusses cultural relations with students. Research conducted in this study is a discussion of literature (library research) where this research uses literature as an object. Some of the literature published from this research is to represent the school culture that is applied by all of schools will then become one of the drivers to become a superior and qualified school, and instill and shape the characters for students to applied at the school, take responsibility, mutually agree to fellow students, agree honestly, politely for the teachers' or for other. Implementing school culture it is necessary to have a good style leadership from the principal, motivate all of school members to be able to apply the existing school culture.